MAN VERSUS TECHNOLOGY - Gonçalves, Claudineia Lima; Regattieri , Carlos Roberto (Revista Interface Tecnológica, 2023)
This developed article addresses the following subject: Man versus Technology. From the second half of the 20th century and now reaching the present time, due to the great development of research regarding the decoding of the genetic map of human beings, and possibly the use of technology and resulting genetic manipulation, some questions have arisen for humanity. Among the questions were about the ethical limits of the involvement of human nature with technology, and another was whether there could be a post-human future, in which it could change the way of human nature through biotechnology and at what points would be found, totally due to natural limitations, diseases and old age. In the scientific and technological field, its advancement enabled man to understand natural phenomena and thus, the diseases that appeared in different times were eradicated, and with a certain discovery, brought man a new vision of human nature. However, if civilizations have acquired the ancient experience of man’s inclination and virtues, and in modernity the progress of excessive actions by inclining them. The purpose of this article will deal with Man versus Technology, in a broad content that seeks to present the most derivative concepts and themes for a better deepening of the proposed title, covering the important issues of today, in order to also provide an understanding in compliance with the that technology instructs human beings to do.